2012
DOI: 10.1016/j.ijmm.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The mglA gene and its flanking regions in Brucella: The role of mglA in tolerance to hostile environments, Fe-metabolism and in vivo persistence

Abstract: We previously demonstrated that a spontaneous smooth small-colony variant of Brucella abortus S19 is characterized by increased in vivo persistence and the differential expression of a gene predicted to encode a galactoside transport ATP binding protein (mglA). In order to further investigate the role of this gene in the context of its flanking regions, we analyzed the respective DNA sequences from the formerly described B. abortus S19 as well as from avirulent B. neotomae 5K33 and compared these with publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…The hypothesis was that high tolerance against oxidative stress as shown most impressively for B. neotomae may positively correlate with the degree of growth and survival in macrophages. The results presented here extend previous findings (Jacob et al 2012 ), i.e., that the B. abortus ∆mglA mutant strain (being more tolerant to H 2 O 2 ) was found in up to 10-fold higher amounts in macrophages when compared to the parental strain B. abortus S19 at 24 h and 48 h after infection in the presence or absence of any preincubation of the macrophages with iron (Fig. 6 ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The hypothesis was that high tolerance against oxidative stress as shown most impressively for B. neotomae may positively correlate with the degree of growth and survival in macrophages. The results presented here extend previous findings (Jacob et al 2012 ), i.e., that the B. abortus ∆mglA mutant strain (being more tolerant to H 2 O 2 ) was found in up to 10-fold higher amounts in macrophages when compared to the parental strain B. abortus S19 at 24 h and 48 h after infection in the presence or absence of any preincubation of the macrophages with iron (Fig. 6 ).…”
Section: Resultssupporting
confidence: 91%
“…In a previous paper investigating the effect of a depletion of the mglA gene (Jacob et al 2006 , 2012 , 2016 ), we demonstrated that the mgl-operon may be an interesting gene region to increase safety and efficacy of the available vaccine strain Brucella abortus S19 . The mutant was characterized by (a) decreased growth on an iron (Fe 2+ )-containing minimal basic medium (Jacob et al 2012 ), (b) an increased tolerance against oxidative stress (H 2 O 2 ), (c) an increased fitness in CRL2471 macrophages, and (d) a significant expression of TNFα, IL1, and IL6 cytokines in CRL2471 macrophages (Jacob et al 2016 ).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations